Post-traumatic acute kidney injury: a cross-sectional study of trauma patients. Issue 1 (December 2016) - Lai, Wei-Hung; Rau, Cheng-Shyuan; Wu, Shao-Chun; Chen, Yi-Chun; Kuo, Pao-Jen; Hsu, Shiun-Yuan; Hsieh, Ching-Hua; Hsieh, Hsiao-Yun
Abstract Background The causes of post-traumatic acute kidney injury (AKI) are multifactorial, and shock associated with major trauma has been proposed to result in inadequate renal perfusion and subsequent AKI in trauma patients. This study aimed to investigate the true incidence and clinical presentation of post-traumatic AKI in hospitalized adult patients and its association with shock at a Level I trauma center. Methods Detailed data of 78 trauma patients with AKI and 14, 504 patients without AKI between January 1, 2009 and December 31, 2014 were retrieved from the Trauma Registry System. Patients with direct renal trauma were excluded from this study. Two-sided Fisher's exact or Pearson's chi-square tests were used to compare categorical data, unpaired Student's t-test was used to analyze normally distributed continuous data, and Mann–Whitney's U test was used to compare non-normally distributed data. Propensity score matching with a 1:1 ratio with logistic regression was used to evaluate the effect of shock on AKI. Results Patients with AKI presented with significantly older age, higher incidence rates of pre-existing comorbidities, higher odds of associated injures (subdural hematoma, intracerebral hematoma, intra-abdominal injury, and hepatic injury), and higher injury severity than patients without AKI. In addition, patients with AKI had a longer hospital stay (18.3 days vs. 9.8 days, respectively;P  < 0.001) and intensive care unit (ICU) stay (18.8 days vs. 8.6 days, respectively;P  < 0. 001), higher proportion of admission into the ICU (57.7% vs. 19.0%, respectively;P  < 0.001), and a higher odds ratio (OR) of short-term mortality (OR 39.0; 95% confidence interval, 24.59–61.82;P  < 0.001). However, logistic regression analysis of well-matched pairs after propensity score matching did not show a significant influence of shock on the occurrence of AKI. Discussion We believe that early and aggressive resuscitation, to avoid prolonged untreated shock, may help to prevent the occurrence of post-traumatic AKI. However, more evidence is required to support this observation. Conclusion Compared to patients without AKI, patients with AKI presented with different injury characteristics and worse outcome. However, an association between shock and post-traumatic AKI could not be identified.